Introduction: women in transition - Williams, C; Blanco, M-J (Routledge, 2021)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book reproduces the interdisciplinary, multi-genre and multicultural nature of the conference through the contributors themselves, from a variety of traditions, backgrounds and countries. It focuses on Bosch’s representation, in which the author experienced an abusive mother–daughter relationship and witnessed her father’s domestic violence towards her mother, which led to bulimia and self-harm. The book navigates multi-layered text by focusing on Bechdel’s descriptions in the area of psychoanalysis, particularly D. W. Winnicott. It investigates the intersection of biography and tourism through analyses of guidebooks dedicated to locations special to two cult women writers from the Portuguese-speaking world.